1992
DOI: 10.1136/bjo.76.6.369
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and orbital recurrence of conjunctival melanoma 21 years after exenteration.

Abstract: In our experience 5% of invasive malignant melanomas of the conjunctiva arising from areas ofprimary acquired melanosis with atypia spread to the ipsilateral nasal cavity and paranasal sinuses. Twenty one years after orbital exenteration for multicentric conjunctival melanoma an 82-year-old man was seen with an orbital recurrence, which had extended to the nasal cavity and paranasal sinuses through the nasolacrimal duct without invading the mucosa. This previously undescribed way of spread after the longest sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…In our case, the patient developed a recurrence 4 years after this procedure. To our knowledge, this kind of recurrence has only been reported once before in a patient who had undergone orbital exenteration 21 years before [6]. …”
Section: Discussionmentioning
confidence: 99%
“…In our case, the patient developed a recurrence 4 years after this procedure. To our knowledge, this kind of recurrence has only been reported once before in a patient who had undergone orbital exenteration 21 years before [6]. …”
Section: Discussionmentioning
confidence: 99%
“…However, typically several conjunctival recurrences occur first, and nasolacrimal recurrences appear at a median of five or six years after initial treatments, 2 , 3 along with recurrences at the nasal passage terminus 4 . Most cancers have hematogenous and lymphatic dissemination patterns, and the lacrimal sac melanoma may have developed within the PAM.…”
Section: Discussionmentioning
confidence: 99%
“…Paridaens et al 4 reported that 5% of invasive conjunctival melanomas arising from areas of PAM with atypia spread locally to the ipsilateral nasal cavity and paranasal sinus. Yet, the patient reported here was never found to have invasive melanoma of the conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
“…Paridaens et al 4 reported that 5% of invasive conjunctival melanomas arising from areas of PAM with atypia spread locally to the ipsilateral nasal cavity and paranasal sinus. Distant metastasis occurs through lymphatic spread through channels in the conjunctival substantia propria or through haematogenous spread 5.…”
Section: Introductionmentioning
confidence: 99%